Pengaruh tingkat kesehatan bank terhadap profitabilitas perusahaan perbankan yang terdaftar di BEI tahun 2016-2020 - Kurniawati, Nita; Bagana, Batara Daniel (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In the world of banking, profitability is important for market participants. The increase in profitability is a good signal for market participants. This study aims to examine the effect of the soundness of banking seen from LDR, NPL, and CAR on profitability. The method used in this research is descriptive quantitative. The analysis technique uses multiple linear regression analysis with the help of the EViews 12 program. The results show that LDR has no effect on profitability, which means that the LDR of banks listed on the IDX does not affect the magnitude of profitability, NPL and CAR have a negative effect on profitability, which means that if the A low NPL indicates that the level of risk in lending to banks is low enough so that the bank will experience profits and the level of profit earned by the bank is not significantly affected by the size of the CAR ratio.